Periodic dark pulse emission induced by delayed feedback in a quantum well semiconductor laser - Li, L. (2013)
We report the experimental observation of periodic dark pulse emission in a quantum-well semiconductor laser with delayed optical feedback. We found that under appropriate operation conditions the laser can also emit a stable train of dark pulses. The repetition frequency of the dark pulse is determined by the external cavity length. Splitting of the dark pulse was also observed. We speculate that the observed dark pulse is a kind of temporal cavity soliton formed in the laser.